A study on corrosion behaviors of laser cladded Fe−Cr−Ni coating in as‐cladded and machined conditions. Issue 4 (20th November 2018) - Zhang, Peirong; Liu, Zhanqiang; Su, Guosheng; Du, Jin; Zhang, Jingjie
Abstract : This paper investigates the effect of turning process on surface quality and corrosion behaviors of laser cladded coatings on the 1045 steel. Corrosion resistance of the 1045 steel is improved by laser cladded Fe−Cr−Ni coatings. The as‐cladded coating behaves nobler and more resistant to corrosion compared to the 1045 steel substrate. By using turning as a finish process, surface roughness Ra of the laser cladded coating is decreased to 0.517 µm to meet the surface roughness requirement (i.e., Ra  ≤ 0.8 µm) of a single‐telescopic hydraulic column. Also, surface defects including laps, cavities, and adhered material particles occur on the cladded coatings after machining. The machined coatings exhibit comparable polarization resistance compared to the as‐cladded condition, and the polarization resistance of the machined surface increases with feed rate increasing. The corrosion pits show sensitivity on feed marks induced by machining. This concentrated distribution of corrosion pits is a result of the fluctuation of local electron work function (EWF), which promotes the formation of local corrosion cells in adjacency to feed marks. Abstract : The effect of turning process on surface quality and corrosion behavior of laser cladded coatings on the 1045 steel was investigated. Corrosion resistance of the 1045 steel is improved by laser cladded Fe–Cr–Ni coatings. The as‐cladded coating behaves nobler and more resistant to corrosion compared to the 1045 steel substrate. By using turning as a finish process, surface roughness Ra of the laser cladded coating is decreased.